A Narrative Analysis of the Social Interaction Process of Young Adult Men Growing Without Fathers - Zufia Ranti; Mutia Rahmi Pratiwi (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
A father has several important roles for the upbringing of his children such as being a role model, teaching his children to be aware of unwritten rules in society, and providing the foundation of communication skills to his children. Unfortunately, some families are not equipped with fathers who have active roles in raising their children or fatherless. This study aimed to analyze the impact of growing up with fathers to a group of men. This study applied a qualitative research design by interviewing four participants. The age range of the participants is from 20-25 years old. These participants have grown without fathers since they were children either because of parental separation or deaths. The findings of this study suggest that fathers have significant roles as the earliest role models for children that help them to adapt to their social environment. The results also indicate some difficulties such as the lack of self-confidence, the struggles to build relationships with people around them, the strains to express emotions, the awkwardness to start conversations with other people and poor communication with both family and peers. The implications of the findings of this study indicate the importance of treating people kindly despite the family status and learning the strategies to communicate thoughts and express emotions better.